The handbook on Caribbean education - Blair, Eleanor; Williams, Kenneth A. (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"The proposed volume brings together leading scholars in Caribbean education to focus on 21st century issues and concerns, specifically as they relate to educational research, theory, policy, and practice. Schooling continues to hold a special place both as a means to achieve social mobility and as a mechanism for supporting the economy of Caribbean nations. For the purposes of this study, the Caribbean will be considered to be the Greater and Lesser Antilles. The Greater Antilles includes the five larger islands (and six countries) of the northern Caribbean, including the Cayman Islands, Cuba, Hispaniola (Haiti and the Dominican Republic), Puerto Rico, and Jamaica. The Lesser Antilles includes the Windward and Leeward Islands which are inclusive of Barbados, St. Vincent, Trinidad and Tobago along with several other islands. As such, each chapter will provide perspectives on the history and sociology of the Caribbean recognizing that each island has its own unique "story." The Handbook will attempt to capture the current breadth and depth of knowledge about Caribbean education while providing a comprehensive description of the current educational landscape and direction for future work and needs. Depending on the response to a call for chapters, the handbook will be organized either by countries or issues. Potential topics include: the politics of language, social justice issues, culturally relevant pedagogy, race and gender issues, teaching profession, technology, leadership, high stakes testing, universal education, inclusive education, safe schools, financing schools etc. The objectives of the book are the following: To describe the intersection of Caribbean education with contemporary global issues and concerns. To identify broad-based foundational research (history and sociology) on Caribbean education. To identify research on key issues (theory, policy and practice) impacting Caribbean schools. To articulate a vision of 21st century Caribbean education. The purposes of the book are the following: The book will fill a vacuum in the literature on 21st century Caribbean education. A book of this type is long overdue and will make a significant contribution to broader, cross-ultural considerations of education. The book will inform efforts to communicate a uniquely Caribbean vision of 21st century schools and education. The book will challenge educators and policy-makers to re-consider the role and place of Caribbean schools in larger political and economic contexts. The proposed book is intended for an academic audience. The authors of the book have extensive experience working and living in the Caribbean. Dr. Blair has been teaching Jamaican teachers (undergraduate and graduate) for 25 years through the Western Carolina University-Jamaica Program. Approximately 100 students participate in this program annually. Dr. Williams Has taught and lived in the Caribbean and is a graduate of Erdiston Teachers' Training College in Barbados, and of the University of the West Indies, Kingston, Jamaica. This book would be a valuable resource for education students at the University of the West Indies in Kingston and in other Caribbean Islands as well as a wide range of post-secondary Caribbean institutions that train teachers. In addition to Caribbean institutions, there are scores of education programs across the Caribbean that are serviced by American universities; this would be a useful resource for these institutions. As such, there is the potential for this book to meet the needs of a large audience of teacher educators"--